Study on online monitoring wear debris sensor of wind turbine gearbox - Xiangqi Zhang; Xiaoli Xu; Yunbo Zuo; Yuhai Gu (The Journal of Engineering, 2019)
Lubrication is one of the critical factors for the normal operation of wind turbine's gearbox, which carries abundant and various wear debris. Accordingly, these debris reflects the running state of the equipment and forecasts the early fault of wind turbine gearbox effectively. Thus, the authors can achieve predictive maintenance, even avoid the occurrence of safety accidents. In order to realise real-time online monitoring of lubrication, this article studied the principle of wear debris detection sensor, constructed approximate mathematical model of inductive wearing debris sensor, produced a prototype device, and carried out the monitoring test of metal wearing debris without oil. Experiment shown that the designed sensor can detect the signal of metal wear debris with the smallest diameter to 80μm, which can diagnose the early fault of the wind turbine.